TINJAUAN YURIDIS ATAS PERTANGGUNGJAWABAN PIDANA PENYALAHGUNAAN IDENTITAS DIGITAL DALAM HUKUM CYBER INDONESIA - Muyassirah Febrianah (Fakultas Hukum Universitas Wiraraja, 2026)
This study investigates criminal liability for individuals who misuse digital identities within the context of cyber law in Indonesia. The development of information technology has given rise to digital identities that serve as a legal representative of a person in the virtual world, but it also poses risks for criminal activities such as data theft, account hacking, identity forgery, and manipulation using artificial intelligence. Although provisions regarding personal data and electronic information are regulated in the Information and Electronic Transactions Law (ITE Law) and reinforced by the Personal Data Protection Law (PDP Law), law enforcement still faces challenges, particularly in terms of evidence and identifying perpetrators. This study applies a normative juridical method with a statutory and conceptual approach to analyze the legal framework that forms the basis of criminal liability for those who misuse digital identities. Research findings indicate that Indonesia already has a framework of norms regulating the protection of digital identity as a legal object, complete with its sanctions. However, the rapid advancement in digital technology, especially in the use of artificial intelligence, has not been fully accounted for in existing criminal regulations, thereby creating a need to update the law so that the protection of digital identity can be better implemented.